Oestrogen receptors and antioestrogen treatment of hormone-dependent tumours - KOSTOMITSOPOULOS (Ν.Γ. ΚΩΣΤΟΜΗΤΣΟΠΟΥΛΟΣ), N. G. (Journal of the Hellenic Veterinary Medical Society, 2018)
The oestrogen receptor is a ligand-activated transcription factor that modulates specific gene expression by binding to short DNA sequences. The study of the role of oestrogen receptor on the expression of the mitogenic actionof oestrogens and oncogenesis lead biomedical research in new approaches of the treatment of oestrogen-dependent tumors by using antioestrogens. Main mechanism of action of antioestrogens is the prevention of oestrogen action by blocking the binding of oestradiol to the oestrogen receptor. Tamoxifen, the most wellknown antioestrogen, is widely used as adjuvant therapy in all stages of human breast cancer. Recently interest is focused on the potential use of "pure" antioestrogens. The use of antioestrogens in veterinary oncology is also under discussion.